Penerapan Sistem Pembayaran SPP Online untuk Meningkatkan Efisiensi Administrasi Keuangan di SMK Techno Media Berbasis Website dengan Model Agile - Anni Tias Lestari; Afrizal Nur Perdana; Rafli Arabiansyah; Wasis Haryono (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
This research seeks to develop a web-based tuition payment system to improve the efficiency of financial administration at SMK Techno Media.The Agile development method was employed, with data collected through observation, interviews, literature review, and documentation. Several challenges were identified, such as delays in processing, inaccuracies in payment information, and inefficiencies in financial reporting. The developed system includes functionalities for generating bills, tracking payment status, sending notifications, and producing financial reports. These features are designed to be utilized by six user roles: administrators, teachers, students, parents, finance staff, and the school principal. The implementation results show notable improvements in data accuracy, information transparency, and administrative efficiency. Furthermore, the system supports digital transformation in the school’s financial management processes.